2001
DOI: 10.3354/ame023301
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ectoenzyme activities as an indication of inorganic nutrient imbalance in microbial communities

Abstract: Assessment of nutrient limitation in microbial populations in marine environments is an important topic. Existing methodologies generally demand long incubations in an experimental assay manipulating nutrients. We suggest a novel approach using the ratio between 2 ectoenzymatic activities, alkaline phosphatase (APA) and aminopeptidase (AMA), to evaluate nutrient limitation of microbial communities in situ. APA is used as an indication of P limitation and AMA of N limitation. The ratio bypasses the use of bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 58 publications
3
89
1
Order By: Relevance
“…However, we do not know if nutrient stress would have increased activity. In the plankton, relatively high LAP activity is often associated with low ratios of N:P, suggesting that the enzyme may be partially inducible (Sala et al 2001). However, changes in LAP activity in natural assemblages may be due to changes in species composition or activity, rather than to induction or suppression of LAP in a species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we do not know if nutrient stress would have increased activity. In the plankton, relatively high LAP activity is often associated with low ratios of N:P, suggesting that the enzyme may be partially inducible (Sala et al 2001). However, changes in LAP activity in natural assemblages may be due to changes in species composition or activity, rather than to induction or suppression of LAP in a species.…”
Section: Discussionmentioning
confidence: 97%
“…However, the contribution of heterotrophic flagellates and cyanobacteria to proteolytic activity in the water column is usually thought to be slight (Martinez & Azam 1993a, Karner et al 1994. The contribution of eukaryotic phytoplankton to protease activity has only recently been considered (Sala et al 2001). Mulholland et al (2002) found that the 'brown tide' alga Aureococcus anophagefferens has high rates of peptide hydrolysis, ABSTRACT: We used the artificial substrate L-leucine 7-amido-4-methyl-coumarin (Leu-AMC) to measure leucine aminopeptidase (LAP) of dinoflagellates.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymatic activities represent a reasonable surrogate of the transformation dynamics by the heterotrophs (Karner and Rassoulzadegan 1995). As a consequence, they may be taken as good indicators of nutrient availability (Sala et al 2001), as well as of detectors of small-scale variations of organic matter use (Romaní and Marxsen 2002).…”
Section: Discussionmentioning
confidence: 99%
“…AMA was determined using fluorogenic substrates (Hoppe 1983(Hoppe , 1993 and followed the modifications described in Sala et al (2001). Briefly, 0.1 ml leucine 7-amido-4-methylcoumarin was added at saturating concentrations (200 µM final concentration) to 0.9 ml samples.…”
Section: Methodsmentioning
confidence: 99%